The relationship between quality of life and anthropometric measurements in premenopausal and postmenopausal among turkish women - Köse, Beril; Yeşil, Esen; Türker, Perim Fatma; Akçil Ok, Mehtap; Bayram, Sinem; Köseler Beyaz, Esra; Özdemir, Merve; Müftüoğlu, Selen; Tayfur, Muhittin; Aksoydan, Emine; Ercan, Aydan; Saka, Mendane; et al. (Progress in Nutrition, 2019)
The aim of this work was to investigate whether there is a relationship between anthropometric measurements and quality of life scores during pre and postmenopouse period. A descriptive study was carried out on 1276 women (40–64 years). Demographic features, socioeconomic attributes and anthropometric measurements were considered using a validated instrument the Turkish version of the EUROHIS (WHOQOL-8.Tr) was performed. Significant body mass index (BMI), height, waist circumference, hip circumference, waist/ height ratio differences were determined by comparing pre and postmenopausal women (p